Penetapan Harga Pokok Produksi Kacang Koro Pedang pada UD Laksmi Devi - NI WAYAN LIA WIDYANTARI; I KETUT SUAMBA; IDA AYU LISTIA DEWI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2018)
Determination of Cost of Goods Manufactured of Jack Beanson UD Laksmi Devi UD Laksmi Devi is an agro-industrial processing of jack beans. The businesscompetition is high, so it is necessary to establish the appropriate best selling price ofproduct through analysis of cost of goods manufactured price of jack beans. Thisstudy aims to find out the cost of jack beans manufactured by UD Laksmi Devi, Theresult of calculation of the cost of goods manufactured based on the components ofproduction costs and non-production costs, compare the difference in the calculationof cost of production from both analysis, and show sensitivity of cost to cost ofgoods of jack beans manufactured with sensitivity analysis. Analysis of cost of goodsmanufactured are calculated only one month, namely December 2016. Calculationof the cost of goods manufactured per unit by UD Laksmi Devi Rp 28.887,33, whilethe value through the analysis of cost of goods manufactured that takes into accountthe components of production and non-production costs amount to Rp 31.529,83.Component of costs incurred by UD Laksmi Devi only production costs, making itlook bigger profits of Rp 22.005.612, compared by researched in the analysis of costof goods manuafactured only Rp 12.492.612. The difference shows that the analysisof cost of goods manufactured based on production costs and non-production costs isgood to applicate because the costs are detailed, so the cost of good manufactured areaccurate as the basic for determining the selling price of jack beans in UD LaksmiDevi.